Simulating the Evolution of Fluid Underpressures in the Great Plains, by Incorporation of Tectonic Uplift and Tilting, with a Groundwater Flow Model. (26th February 2018) - Umari, Amjad M. J.; Nelson, Philip H.; Fridrich, Chris; LeCain, Gary D.
Abstract : Underpressures (subhydrostatic heads) in the Paleozoic units underlying the Great Plains of North America are a consequence of Cenozoic uplift of the area. Based on tectonostratigraphic data, we have developed a cumulative uplift history with superimposed periods of deposition and erosion for the Great Plains for the period from 40 Ma to the present. Uplift, deposition, and erosion on an 800 km geologic cross-section extending from northeast Colorado to eastern Kansas is represented in nine time-stepped geohydrologic models. Sequential solution of the two-dimensional diffusion equation reveals the evolution of hydraulic head and underpressure in a changing structural environment after 40 Ma, culminating in an approximate match with the measured present-day values. The modeled and measured hydraulic head values indicate that underpressures increase to the west. The 2 to 0 Ma model indicates that the present-day hydraulic head values of the Paleozoic units have not reached steady state. This result is significant because it indicates that present-day hydraulic heads are not at equilibrium, and underpressures will increase in the future. The pattern uncovered by the series of nine MODFLOW models is of increased underpressures with time. Overall, the models indicate that tectonic uplift explains the development of underpressures in the Great Plains.